Palynostratigraphy of the early Paleogene at the Laguna Manantiales locality, southern Golfo San Jorge Basin, Argentina - Quattrocchio, Mirta Elena (2024)
This study focuses on the early Paleogene deposits of the southernmost Golfo San Jorge Basin (central Patagonia, Argentina), cropping out at the Laguna Manantiales site. Based on palynological and sedimentological features, a new continental stratigraphic unit, informally named as Laguna Manantiales Strata, is here defined. The sporomorphs recorded evidence of the presence of subtropical forests. The syncolporate pollen grains comparable to those of the modern taxon Senna pendula, are mentioned for the first time in Argentina. Based on the record of Malvacipollis diversus, Bombacacidites isoreticulatus, Cricotriporites guianensis and the similarity in the pollen grains composition, the identified palynological assemblage can be correlated to the Patagonian palynofloras from the late Paleocene–early Eocene Ligorio Márquez Formation and the early Eocene Laguna del Hunco site. Thus, the proposed age for the Laguna Manantiales Strata can be constrained between the late Paleocene and the early Eocene. The records of Huanilipollis cabrerae, H. crisci, and Mutisiapollis sp. in Laguna Manantiales Strata, confirm the early development for Mutisioideae for the early Paleogene in Patagonia. The pronounced climatic warming during the late Paleocene and the early Eocene influenced the diversification of Asteraceae in Patagonia.